2020
DOI: 10.1186/s12888-020-02948-8
|View full text |Cite
|
Sign up to set email alerts
|

The association between depressive symptoms and self-rated health among university students: a cross-sectional study in France and Japan

Abstract: Background Depressive disorders in University students have risen dramatically in the past few decades to the extent that students’ mental health has become a current global public health priority. Obtaining information from University students about their mental health is challenging because of potential embarrassment of disclosing one’s concerns and fear of stigmatization. Self-rated health might be a good solution to evaluate mental health state by a simple and neutral indicator. The aim of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 35 publications
2
17
0
Order By: Relevance
“…According to the report of Hossain et al (2020), poor Self-perceived health was found to be significantly associated with a higher likelihood of depression and anxiety among students (Hossain et al, 2020b). A cross-sectional study conducted using two large cohorts of students in France and Japan by Ishida et al (2020) showed that high depressive symptoms and poor selfrated health were strongly associated, independently of all other variables (Ishida et al, 2020). Similarly, result from an online survey during the COVID-19 pandemic among nursing and midwifery students suggested that those having poorer self-rated general health were all significantly associated with higher scores on at least one DASS-21 subscale (Wynter et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…According to the report of Hossain et al (2020), poor Self-perceived health was found to be significantly associated with a higher likelihood of depression and anxiety among students (Hossain et al, 2020b). A cross-sectional study conducted using two large cohorts of students in France and Japan by Ishida et al (2020) showed that high depressive symptoms and poor selfrated health were strongly associated, independently of all other variables (Ishida et al, 2020). Similarly, result from an online survey during the COVID-19 pandemic among nursing and midwifery students suggested that those having poorer self-rated general health were all significantly associated with higher scores on at least one DASS-21 subscale (Wynter et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The validity and reliability of the five-point Likert scale of SRH have been widely confirmed [39,40]. With reference to similar work [41], this variable was further divided into two categories: "good" (including "excellent", "very good" or "good") and "fair or poor" (including "fair" or "poor") SRH.…”
Section: Exposure Measurementmentioning
confidence: 94%
“…SRH is a subjective measure of health status that integrates a person's biological, psychological, social, and functional aspects; and has been widely used in epidemiological studies ( 1 , 5 , 26 ). In this study, SRH was assessed by five-point Likert scale of self-rated health corresponding: “How do you feel about your health in general?” ( 27 , 28 ), and the options were divided into 5 groups (1 = very good, 2 = good, 3 = fair, 4 = poor, 5 = very poor) ( 6 ). Referring to the standards of other international cohort study ( 29 ), those with a score of 3–5 were defined as suboptimal SRH, and those with a score of 1 or 2 were defined as good SRH.…”
Section: Methodsmentioning
confidence: 99%